Role of large unstained cells in predicting successful stem cell collection in autologous stem cell transplantation - Merter, Mustafa; Sahin, Ugur; Uysal, Serhat; Dalva, Klara; Yuksel, Meltem Kurt (Pergamon-Elsevier Science Ltd, 2023)
Introduction: Sufficient stem cell collection is mandatory for Autologous stem cell transplantation (ASCT). Peripheral CD34+ stem CD34 + stem cell counting by flow cytometry is the gold standard method in both the predicting and timing of successful stem cell collection. Large unstained cells (LUC) are large peroxidase-negative cells that are displayed on certain automatic cell counters and present large lymphocytes, virocytes, blasts, abnormal cells and hematopoietic stem cells. In this study, we evaluated the role of LUC parameters in the timing and prediction of successful stem cell collection. Methods: Patients with a diagnosis of multiple myeloma, lymphoma and testis tumor who proceed to ASCT were included in this study. Preapheresis LUC parameters were analyzed with Siemens ADVIA (R) 2120i system., Kruskal Wallis, Mann-Whitney U, Spearman Rho and receiver-operator curve (ROC) tests were used for analyses. Results: Ninety patients were evaluated. Peripheral CD34 + cell count was positively correlated with both LUC count (p = 0014) and LUC percentage (p = 0,01). LUC percentage in peripheral blood was positively correlated with mobilized stem cell count in the yield (p = 0.003). We found a LUC count of > 0.485 x 109 /L as a cut-off value for detecting > 20 x 106 /L CD34 +cells in the peripheral blood with a sensitivity of 64.6% and specificity of 75%. We defined > 2.15% as a cut-off value for LUC percentage to collect > 5 x 106 /kg of stem cells with a sensitivity of 64% and specificity of 63%. Additionally, total nucleated cell (TNC) count was negatively correlated with LUC percentage (p = 0.014) and positively correlated with LUC count (p = 0.001). Conclusion: LUC parameters are readily available, simple and cheap tools that can be useful in both timing of CD34 count by flow cytometry in peripheral blood and in the prediction of successful mobilization. LUCs can also be an indicator of graft composition.
Keywords: Large unstained cells; LUC; Stem cell mobilization; Stem cell collection; TNC; MNC